Motion model for describing the quantity of air in droplets through changing the structure of air induction nozzle - Hu, Jun; Liu, Changxi; Wang, Zhichong; Li, Yufei; Song, Jianli; Liu, Yajia; Chu, Xin (International Journal of Agricultural and Biological Engineering, 2021)
Air induction nozzles possess good anti-drift performance, the throat and orifice sizes of the nozzles are main design parameters that affecting atomization. Therefore, Venturi tube nozzles and conventional flat fan nozzles were assembled together to investigate the flow rate, droplet size, the quantity of air in droplets affected by single design parameter of nozzles with applying high speed camera and Spraytec laser diffraction system. The results showed that: the flow rate of the air induction nozzle depended only on the throat size of Venturi tube and pressure, and it was proportional to the throat size of Venturi tube at the same pressure; The flat fan nozzle’s orifice size and Venturi tube size significantly affected volume median diameter of droplets, which generally increased after adding surfactant; A new model was established after optimizing classical equation for calculating the percentage of intake air in droplets and studying the effects of throat and orifice size of air induction nozzles on spray characteristics. By variance analysis, it was verified that the new model of quantity of air in droplets produced by all connected nozzles was correct. The calculation showed that the bubbles sizes ranged at 200-900 μm and were in proportion to the droplet size with the percentage of intake air of 10% to 90%. Contrast to the change of volume median diameter and droplet velocity, existence of intake air could influence their change degree to some extent.Keywords: throat orifice, spray characteristic, model of droplet motion, air induction nozzleDOI: 10.25165/j.ijabe.20211405.5513Citation: Hu J, Liu C X, Wang Z C, Li Y F, Song J L, Liu Y J, et al. Motion model for describing the quantity of air in droplets through changing the structure of air induction nozzle. Int J Agric & Biol Eng, 2021; 14(5): 35–40.